Pedagogical processes to make reading and writing productive activities - Colmenares Acosta, Juana; Florez Prada, Gloria Patricia; Barrera Serrano, Edith; Salazar Real, Fidelina (Rastros Rostros, 2023)
Reading and writing are not simple processes of decoding or encoding texts; on the contrary, these activities require a high level of processing in which acts of meaning, interpretation and comprehension are involved.